English Language Teachers’ Perceptions of the Mobile Assisted Language Learning at a Saudi Arabian University: Opportunities and Challenges - Pir Suhail Ahmed Sarhandi, Victor N Teise, Firdous Bugti (PJDOL, 2022)
Accessibility of mobile phones has offered prospects for researchers to discover their influence on education. English language teaching is not exclusive in this matter. This research was conducted to understand how English language teachers at Saudi Arabian university were adopting mobile learning in classrooms